Characterization of dermatological diseases in canines treated at the Veterinary Hospital of the University of San Carlos of Guatemala - Farfán-Arbizú, Bárbara Anarosi (2020)
A retrospective study of canine patients with dermatopathies treated at the Veterinary Hospital of the Faculty of Veterinary Medicine and Zootechnics of the University of San Carlos of Guatemala in 2017 was carried out. The diseases were classified using the DAMNITIV rule, and considering the variables sex, age and breed. The prevalence of dermatopathies was 27.1% (n=305). The most frequent pathologies were neoplasms, followed by infectious and allergic agents. The greatest casuistry was represented by canines of undefined breed and in females. The average age of affected patients was 6.9 ± 0.2 years.